Mitochondrial dynamics and the cell cycle - Kianian, Penny M. A.; Kianian, Shahryar F. (Frontiers in Plant Science, 2014)
Nuclear-mitochondrial (NM) communication impacts many aspects of plant development including vigor, sterility and viability. Dynamic changes in mitochondrial number, shape, size, and cellular location takes place during the cell cycle possibly impacting the process itself and leading to distribution of this organelle into daughter cells. The genes that underlie these changes are beginning to be identified in model plants such as Arabidopsis. In animals disruption of the drp1 gene, a homolog to the plant drp3A and drp3B, delays mitochondrial division. This mutation results in increased aneuploidy due to chromosome mis-segregation. It remains to be discovered if a similar outcome is observed in plants. Alloplasmic lines provide an opportunity to understand the communication between the cytoplasmic organelles and the nucleus. Examples of studies in these lines, especially from the extensive collection in wheat, point to the role of mitochondria in chromosome movement, pollen fertility and other aspects of development. Genes involved in NM interaction also are believed to play a critical role in evolution of species and interspecific cross incompatibilities.